Wake-up call for British psychiatry. - Craddock, N; Antebi, D; Attenburrow, M; Bailey, A; Carson, A; Cowen, P; Craddock, B; Eagles, J; Ebmeier, K; Farmer, A; Fazel, S; Ferrier, N; et al. (2008)
The recent drive within the UK National Health Service to improve psychosocial care for people with mental illness is both understandable and welcome: evidence-based psychological and social interventions are extremely important in managing psychiatric illness. Nevertheless, the accompanying downgrading of medical aspects of care has resulted in services that often are better suited to offering non-specific psychosocial support, rather than thorough, broad-based diagnostic assessment leading to specific treatments to optimise well-being and functioning. In part, these changes have been politically driven, but they could not have occurred without the collusion, or at least the acquiescence, of psychiatrists. This creeping devaluation of medicine disadvantages patients and is very damaging to both the standing and the understanding of psychiatry in the minds of the public, fellow professionals and the medical students who will be responsible for the specialty's future. On the 200th birthday of psychiatry, it is fitting to reconsider the specialty's core values and renew efforts to use psychiatric skills for the maximum benefit of patients.